Suspended Sediments in Chilean Rivers Reveal Low Postseismic Erosion After the Maule Earthquake (Mw 8.8) During a Severe Drought. Issue 6 (5th June 2019) - Tolorza, Violeta; Mohr, C. H.; Carretier, S.; Serey, A.; Sepúlveda, S. A.; Tapia, J.; Pinto, L.
Abstract: We address the question of whether all large‐magnitude earthquakes produce an erosion peak in the subaerial components of fluvial catchments. We evaluate the sediment flux response to the Maule earthquake in the Chilean Andes (Mw 8.8) using daily suspended sediment records from 31 river gauges. The catchments cover drainage areas of 350 to around 10, 000 km 2, including a wide range of topographic slopes and vegetation cover of the Andean western flank. We compare the 3‐ to 8‐year postseismic record of sediment flux to each of the following preseismic periods: (1) all preseismic data, (2) a 3‐year period prior to the seismic event, and (3) the driest preseismic periods, as drought conditions prevailed in the postseismic period. Following the earthquake, no increases in suspended sediment flux were observed for moderate to high percentiles of the streamflow distribution (mean, median, and ≥75th percentile). However, more than half of the examined stations showed increased sediment flux during baseflow. By using a Random Forest approach, we evaluate the contributions of seismic intensities, peak ground accelerations, co‐seismic landslides, hydroclimatic conditions, topography, lithology, and land cover to explain the observed changes in suspended sediment concentration and fluxes. We find that the best predictors are hillslope gradient, low‐vegetation cover, and changes in streamflow discharge. This finding suggests a combined first‐order control of topography, land cover, and hydrology on the catchment‐wide erosion response. We infer a reduced sediment connectivity due to the postseismic drought, which increased the residence time of sediment detached and remobilized following the Maule earthquake. Key Points: Postseismic suspended sediment fluxes decreased during moderate‐ to high‐flow conditions with respect to background values A reduced hillslope‐channel connectivity due to drought and limited coseismic landsliding set the catchment‐wide erosive response During postseismic dry conditions, the first‐order control on catchment‐wide erosion is the combined effect of topography and land cover